Decompressive craniectomy as primary therapy for cranial hypertension due to head trauma: Observational experience in 24 patients - León-Palacios, José Luis (2021)
Introduction: Head trauma is one of the main causes of death in Peru. Medical and surgical therapy during the initial stages of severe head trauma focus in preventing the elevation of intracranial pressure. Objective: To describe the associated characteristics and main complications in patients undergoing decompressive craniectomy. Methods: This is a retrospective observational study performed between February 2018 and July 2020 in patients who had been admitted because of head trauma and who had undergone unilateral decompressive craniectomy. Results: Two-thirds (66.7%) of patients were persons less than 40 years of age; 87.5% were males; 16.7% were admitted with Glasgow Coma Score (GCS) scores between 13 and 15; 37.5% were admitted with GCS between 9 and 12; 42.9% had asymmetric pupils; 33.3% were admitted because of traffic accidents; 21.7% were Marshall II, 65.2% were Marshall III, and 13.0% were Marshall IV. Conclusions: Our results suggest that characteristics associated to decompressive craniectomy because of head trauma contribute for its proper management.